2017
DOI: 10.1186/s12284-017-0172-3
|View full text |Cite
|
Sign up to set email alerts
|

Sugary Endosperm is Modulated by Starch Branching Enzyme IIa in Rice (Oryza sativa L.)

Abstract: BackgroundStarch biosynthesis is one of the most important pathways that determine both grain quality and yield in rice (Oryza sativa L.). Sugary endosperm, sugary-1 (sug-1), is a mutant trait for starch biosynthesis. Rice plants carrying sug-1 produce grains that accumulate water-soluble carbohydrates instead of starch, even after maturity. Although this trait enhances the diversity of grain quality, sugary endosperm rice has hardly been commercialized due to the severely wrinkled grains and subsequent proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
(59 reference statements)
1
17
0
Order By: Relevance
“…It is thought to be involved in the initiation step of starch biosynthesis in the rice endosperm, although Pho1 can also function to degrade glucan (Satoh et al, 2008). In addition to the above-mentioned starch biosynthetic isozymes, SSIVb (Toyosawa et al, 2016), BEIIa (Satoh et al, 2003; Lee et al, 2017), and the disproportionating enzyme (EC 2.4.1.25) (Dong et al, 2015) are also involved in amylopectin biosynthesis in the rice endosperm.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought to be involved in the initiation step of starch biosynthesis in the rice endosperm, although Pho1 can also function to degrade glucan (Satoh et al, 2008). In addition to the above-mentioned starch biosynthetic isozymes, SSIVb (Toyosawa et al, 2016), BEIIa (Satoh et al, 2003; Lee et al, 2017), and the disproportionating enzyme (EC 2.4.1.25) (Dong et al, 2015) are also involved in amylopectin biosynthesis in the rice endosperm.…”
Section: Introductionmentioning
confidence: 99%
“…A loss-of-function mutation of the gene encoding DBE results in a sugary phenotype in which endosperm starch is completely replaced by phytoglycogen [52,53]. Mutant sug-h, which is defective in OsISA1 and OsBEIIa, exhibits a severely disrupted amylopectin structure [54].…”
Section: Discussionmentioning
confidence: 99%
“…A study on the kidney bean (Phaseolus vulgaris) mutant pvsbe2 suggested that SBEII activity is important for both amylopectin biosynthesis and maturation during the middle and late stages of seed development 22 . Further, the expression of OsSBEIIa was found to regulate the sugary endosperm trait during development and maturity in the Sugary Endosperm rice mutant 23 . In maize, SBEIIadefective mutants exhibit a leaf-senescence phenotype as the result of the reduction in the proportion of branched starch 24 .…”
Section: Introductionmentioning
confidence: 95%